Absidia thailandica sp. nov., an addition to the diversity of soil fungi from Thailand - Htet, Yee Mon; Yasanthika, W. A. Erandi; Hurdeal, Vedprakash G.; Gomes De Farias, Antonio Roberto (Phytotaxa, 2024)
Absidia is ubiquitous and plays a critical function in biotechnology and medicine. It is characterized by single sporangiophores, in pairs or groups on stolons, bearing apophysate and pyriform sporangia with a deliquescent wall. This study isolated and proposed Absidia thailandica sp. nov. as an addition to Mucorales from Thailand. Phylogenetic analyses of IITS + LSU rDNA data showed that this species is related to A. ovalispora and A. soli. However, it differs from A. ovalispora by the absence of swollen parts on the sporangiophores and shape of rhizoids and can be distinguished from A. soli by the shape of rhizoids, size of sporangiospores and shape and size of columellae. This study expands the diversity of soil fungi in Thailand.